Epidemiology, pathogenesis, and emerging concepts in unruptured intracranial aneurysms: unruptured intracranial aneurysms 1 - Etminan, Nima; Ruigrok, Ynte M.; Hackenberg, Katharina; Vergouwen, Mervyn D. I.; Krings, Timo; Rinkel, Gabriel J. E. (The lancet, 2025)
About 3% of adults have an unruptured intracranial aneurysm and this prevalence can increase to 10% in high-risk groups. Aneurysms are not congenital, but develop throughout life. New evidence has established that genetic, anatomical, inflammatory, and modifiable risk factors interact in the formation, growth, and rupture of aneurysms. Genome-wide association studies have found an association with genetic risk variants in 17 loci. Furthermore, circle of Willis variations predispose to aneurysm formation and cluster within families. These variations, plus modifiable risk factors, such as hypertension and smoking, result in haemodynamic stress and inflammatory reactions in the vessel and aneurysm wall but, in people at high risk, aneurysms can also form in the absence of hypertension or smoking. These research advances provide knowledge bases for the individualised concepts of identifying individuals who can have an aneurysm or patients with aneurysms at increased risk of rupture, and for pharmacological treatments for patients who do not require immediate preventive repair.
Gesehen am 03.12.2025